Influences of age and pubertal status on number and intensity of perineuronal nets in the rat medial prefrontal cortex - Drzewiecki, Carly M.; Willing, Jari; Juraska, Janice M. (Brain structure & function, 2020)
The prefrontal cortex (PFC) is a late developing region of the cortex, and its protracted maturation during adolescence may confer a period of plasticity. Closure of critical, or sensitive, periods in sensory cortices coincides with perineuronal net (PNN) expression, leading to enhanced inhibitory function and synaptic stabilization. PNN density has been found to increase across adolescence in the male rat medial PFC (mPFC). Here, we examined both male and female rats at four time points spanning adolescent development to stereologically quantify the number and intensity of PNNs in the mPFC. Additionally, because puberty coincides with broad behavioral and neuroanatomical changes, we collected tissue from age-matched pre- and post-pubertal siblings within a litter. Results indicate that both males and females show an increase in the total number and intensity of mPFC PNNs between postnatal day (P) 30 and P60. As we have previously found, white matter under the mPFC also increased at the same time. Male puberty did not affect PNNs, while female pubertal onset led to an abrupt decrease in the total number of PNNs that persisted through mid-adolescence before increasing at P60. Despite the change in PNN number, the intensity of female PNNs was not affected by puberty. Thus, though males and females show increases in mPFC PNNs during adolescence, the pubertal decrease in the number of PNNs in female rats may indicate a difference in the pattern of maximal plasticity between the sexes during adolescence.